أثر نسب كفاية وكفاءة التدفقات النقدية التشغيلية على ربحية المؤسسات الصناعية الجزائرية: دراسة حالة مجموعة من المؤسسات خلال الفترة 2011 – 2015. - زواويد, لزهاري; قريشي, بلقاسم (جامعة الوادي University of Eloued, 2019)
This study aims to determine the impact of the Sufficiency and efficiency Ratios of operating cash flows on the profitability of Algerian industrial institutions during the period 2011-2015 through the use of the Panal longitudinal regression model and using the Eviews 09 program used to explain and find the impact between operating cash flow ratios and profitability indicators, and the study sample included 60 industrial institutions. This study was concluded a different effect of net operating cash flows and some Sufficiency and efficiency ratios on the profitability indices, So that we have finally found an effect between net operating cash flows and impact of the ratio of net operating cash flows to total liabilities and equity and the current liabilities on profitability indices, While there was no effect of the other ratios used in this study on the indicators of profitability
The impact of the Sufficiency and efficiency Ratios of operating cash flows on the profitability of Algerian industrial institutions A case study of a group of institutions during the period 2011-2015
مقال
Keywords: تدفقات نقدية تشغيلية؛ نسب كفاية؛ نسب كفاءة؛ ربحية؛ مؤسسات صناعية.; Operating Cash Flows; Sufficiency Ratios; Efficiency Ratios; Profitability; Industrial institutions.